Reflection of the service encounter environment in enhancing customer satisfaction - جثير الربيعاوي سعدون حمود; عبد العبادي فارس احمد (Journal of Economics and Administrative Sciences, 2020)
Because of the fierce competition between service organizations on the one hand and the increasing demands of customers on the other. Therefore, these organizations sought to distinguish their service by taking care of all aspects. One of these important aspects is the service encounter environment and its reflection on customer emotions, so we choose the current research to clarify the importance and impact on customer satisfaction, the problem of research is how the interest of Iraqi restaurants in the service encounter environment and how to care about its elements and whether this interest is sufficient to reflect the satisfaction of the customer. the goal of the current research was to clarify how much the application of the environment of meeting services in restaurants and to determine the degree of influence of the independent variable in the dependent. In order to reach this goal, three main hypotheses were formulated, the first one was (there is a significant correlation between the service encounter environment and customer satisfaction),The second was (there is a effect for the service encounter environment in customer satisfaction), While the third hypothesis was (there is an effect for the dimensions of the service encounter environment combined customer satisfaction , the research target was service sector, especially the Iraqi restaurant sector, the search community is the customers in the restaurants of the excellent grade, Sample search (346) customers, As for data collection, the questionnaire was used as a main tool, personal interviews and personal observation of the researcher in the field as secondary tools either the statistical program (SPSS_V.19) was used to analyze data, as well as the use of a set of statistical means such as arithmetic mean, standard deviation, coefficient of variation to analyze and describe Data, correlation coefficient Pearson to test correlation hypotheses, the equation of simple linear regression, and the equation of multiple linear regression to test the hypotheses of impact, and finally the research reached a set of conclusions, the Iraqi restaurants of the is interested in service encounter environment with some obstacles that have to be made up for, has recommended the promotion of research orientation and attention to service encounter environment because of its significant role in the interpretation of customer satisfaction